Peringatan Hari Kemerdekaan Sebagai Upaya Penguatan Moderasi Beragama di Dusun Gupit - Erly Rizky Kamalia; Lailatun Nadipah (LP3M IAIFA Kediri, 2025)
The promotion of religious moderation is crucial to be implemented in Dusun Gupit, considering the religious diversity among its residents, who consist of both Muslims and Buddhists. Following the